HEALING HUB BATU CITY : A Journey to the Serenity of Mind - Tyastuti Cahyani Pancaputri; Erna Winansih; Etikawati Triyosoputri; Raqyan Mas Bimatyugra Jati (Architecture Study Program, Faculty Of Engineering, University of Merdeka Malang, 2025)
The fast-paced nature of modern life often leads to acute stress, which can trigger mental health issues, especially among young adults experiencing a quarter-life crisis. In response, Healing Hub Kota Batu is designed as a holistic healing center that nurtures the mind, body, and soul. Carrying the theme Journey to the Serenity of Mind, this project aims to create a tranquil environment that promotes self-healing through architectural design. Guided by the Optimal Healing Environment (OHE) concept, the design focuses on reducing stress, enhancing relaxation, and fostering a connection with nature. Key design strategies include biophilic design, therapeutic landscapes, and sensory architecture. Green open spaces, water elements, and natural lighting are integrated to create a calming atmosphere that supports mental recovery. The design methodology involves qualitative research, including site analysis, case studies, and literature reviews on OHE principles. A human-centered approach ensures user comfort and functionality. Through this approach, Healing Hub Kota Batu is envisioned as a pioneering wellness center that serves the local community and attracts regional, national, and international visitors seeking holistic mental well-being solutions.